Creating AI Art Responsibly: A Field Guide for Artists - Claire Leibowicz; Emily Saltz; Lia Coleman (Diseña, 2021)
Machine learning tools for generating synthetic media enable creative expression, but they can also result in content that misleads and causes harm. The Responsible AI Art Field Guide offers a starting point for designers, artists, and other makers on how to responsibly use AI techniques and in a careful manner. We suggest that artists and designers using AI situate their work within the broader context of responsible AI, attending to the potentially unintended harmful consequences of their work as understood in domains like information security, misinformation, the environment, copyright, and biased and appropriative synthetic media. First, we describe the broader dynamics of generative media to emphasize how artists and designers using AI exist within a field with complex societal characteristics. We then describe our project, a guide focused on four key checkpoints in the lifecycle of AI creation: (1) dataset, (2) model code, (3) training resources, and (4) publishing and attribution. Ultimately, we emphasize the importance for artists and designers using AI to consider these checkpoints and provocations as a starting point for building out a creative AI field, attentive to the societal impacts of their work.